2014
DOI: 10.4103/0019-5049.135035
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal intubation in patients with cervical spine immobilization: A comparison of McGrath ® video laryngoscope and Truview EVO2 ® laryngoscope

Abstract: Background and Aims:Literature suggests that glottic view is better when using McGrath® Video laryngoscope and Truview® in comparison with McIntosh blade. The purpose of this study was to evaluate the effectiveness of McGrath Video laryngoscope in comparison with Truview laryngoscope for tracheal intubation in patients with simulated cervical spine injury using manual in-line stabilisation.Methods:This prospective randomised study was undertaken in operation theatre of a tertiary referral centre after approval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
0
11
1
Order By: Relevance
“…Bag et al found the mean time necessary for intubation equaled 21.10 ± 5.64 seconds for Truview and 15.79 ± 2.76 seconds for Macintosh [11]. A clinical study conducted by Bhola et al comparing McGrath and Truview PCD reported that the time to successful intubation was shorter with the McGrath video laryngoscope when compared with Truview (30.02 seconds versus 38.72 seconds) but there was no significant difference between the laryngoscopic views obtained in both groups [15]. Singh et al published the results of their study on intubation using Truview PCD, C-MAC, and Macintosh laryngoscopes in paediatric patients.…”
Section: Discussionmentioning
confidence: 98%
“…Bag et al found the mean time necessary for intubation equaled 21.10 ± 5.64 seconds for Truview and 15.79 ± 2.76 seconds for Macintosh [11]. A clinical study conducted by Bhola et al comparing McGrath and Truview PCD reported that the time to successful intubation was shorter with the McGrath video laryngoscope when compared with Truview (30.02 seconds versus 38.72 seconds) but there was no significant difference between the laryngoscopic views obtained in both groups [15]. Singh et al published the results of their study on intubation using Truview PCD, C-MAC, and Macintosh laryngoscopes in paediatric patients.…”
Section: Discussionmentioning
confidence: 98%
“…The intubation times recorded in our study were similar to that found in previous studies for inexperienced providers, uncomplicated ETI and ETI with MILNS. Bhalla et al [5] prospectively compared the use of the McGarth and Truview VL systems in patients with MILNS applied throughout airway management in the operating room. The authors reported mean intubation times ranging between 30.02 and 38.72 s for the respective devices.…”
Section: Discussionmentioning
confidence: 99%
“…However, VL utilises a different psychomotor skill-set compared to DL, requires specific training [4] and familiarisation with the specific VL system itself. This can be argued as shown by the variability of performance between devices [5] , [6] , [7] . This is a concern in paramedic educational programs, as dilution of DL practice through the overuse of VL may result in DL skills attrition, which remains the standard rescue airway management option of choice when VL is not successful [8] .…”
Section: Introductionmentioning
confidence: 99%
“…More patients (16/50) required additional manoeuvres to improve glottis view in group ML than other groups. Improvement in Cormack and Lehane grade at least by one has been reported during both routine and difficult airway scenarios [13][14][15][16] while laryngoscopy with Airtraq and Trueview laryngoscopes.…”
Section: Discussionmentioning
confidence: 99%